NOP01, a NOP receptor agonist, produced potent and peripherally restricted antinociception in a formalin-induced mouse orofacial pain model. (February 2022) - Xiao, Jian; Niu, Jiandong; Xu, Biao; Zhang, Run; Zhang, Mengna; Zhang, Nan; Xu, Kangtai; Zhang, Qinqin; Chen, Dan; Shi, Yonghang; Fang, Quan; Li, Ning
Abstract: Orofacial pain is one of the most common medical challenges. A preliminary report indicates that the NOP receptor may act as a therapeutic target in orofacial pain. Previous studies have shown that [(pF)Phe 4, Aib 7, Aib 11, Arg 14, Lys 15 ]N/OFQ-NH2 (NOP01) functions as a potent NOP receptor peptide agonist. This work aims to investigate the antinociception of NOP01 and its possible action mechanisms in a formalin-induced mouse orofacial pain model at different levels. Our results demonstrated that local, intraperitoneal (i.p.) or intrathecal (i.t.) injection of NOP01 produced dose-related antinociception in both phases of the formalin pain, which could be inhibited by the NOP receptor antagonist but not the classical opioid receptor antagonist. Furthermore, the antinociception induced by systemic NOP01 was blocked by local but not spinal pretreatment with the NOP receptor antagonist, suggesting the involvement of the peripheral NOP receptor in NOP01-induced systemic antinociception. Moreover, local injection of NOP01 markedly suppressed the expression of c-Fos protein induced by formalin in ipsilateral trigeminal ganglion (TG) neurons. In conclusion, this work suggests that NOP01 exerts significant antinociception on orofacial pain at both peripheral and spinal levels via the NOP receptor. Notably, NOP01 cannot readily penetrate the blood-brain barrier. Thus, NOP01 may behave as a potential compound for developing peripherally restricted analgesics.